Cannabinoid receptor type I modulates alcohol-induced liver fibrosis - Patsenker, Eleonora; Stoll, Matthias; Millonig, Gunda; Agaimy, Abbas; Wissniowski, Till; Schneider, Vreni; Mueller, Sebastian; Brenneisen, Rudolf; Seitz, Helmut K.; Ocker, Matthias; Stickel, Felix (Molecular medicine, 2011)
The cannabinoid system (CS) is implicated in the regulation of hepatic fibrosis, steatosis and inflammation, with cannabinoid receptors 1 and 2 (CB1 and CB2) being involved in regulation of pro- and antifibrogenic effects. Daily cannabis smoking is an independent risk factor for the progression of fibrosis in chronic hepatitis C and a mediator of experimental alcoholic steatosis. However, the role and function of CS in alcoholic liver fibrosis (ALF) is unknown so far. Thus, human liver samples from patients with alcoholic liver disease (ALD) were collected for analysis of CB1 expression. In vitro, hepatic stellate cells (HSC) underwent treatment with acetaldehyde, Δ9-tetrahydrocannabinol H₂O₂, endo- and exocannabinoids (2-arachidonoylglycerol (2-AG) and [THC]), and CB1 antagonist SR141716 (rimonabant). In vivo, CB1 knockout (KO) mice received thioacetamide (TAA)/ethanol (EtOH) to induce fibrosis. As a result, in human ALD, CB1 expression was restricted to areas with advanced fibrosis only. In vitro, acetaldehyde, H₂O₂, as well as 2-AG and THC, alone or in combination with acetaldehyde, induced CB1 mRNA expression, whereas CB1 blockage with SR141716 dose-dependently inhibited HSC proliferation and downregulated mRNA expression of fibrosis-mediated genes PCα1(I), TIMP-1 and MMP-13. This was paralleled by marked cytotoxicity of SR141716 at high doses (5-10 μmol/L). In vivo, CB1 knockout mice showed marked resistance to alcoholic liver fibrosis. In conclusion, CB1 expression is upregulated in human ALF, which is at least in part triggered by acetaldehyde (AA) and oxidative stress. Inhibition of CB1 by SR141716, or via genetic knock-out protects against alcoholic-induced fibrosis in vitro and in vivo.
Gesehen am 23.09.2022